1997
DOI: 10.1103/physreva.56.r4393
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction electron-atom scattering in an intense low-frequency laser field

Abstract: An explanation of discrepancies between predictions of the Kroll-Watson theory and cross sections measured in the Wallbank-Holmes experiments on electron-atom scattering in the presence of a powerful lowfrequency laser field is presented. Our model calculations for helium and argon as target atoms come out to be in good agreement with experimental results; i.e., obtained cross sections are by many orders of magnitude larger than those predicted by the Kroll-Watson theory. A mechanism responsible for such a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Their result for two photon exchange is several orders of magnitude higher, however. This may be due to a convergence issue, as a group using a similar method for laser-assisted helium scattering at first found high cross sections [11], but later found better results that are closer to the KWA [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their result for two photon exchange is several orders of magnitude higher, however. This may be due to a convergence issue, as a group using a similar method for laser-assisted helium scattering at first found high cross sections [11], but later found better results that are closer to the KWA [18].…”
Section: Resultsmentioning
confidence: 99%
“…)It can be shown that the first variation δb[Ψ β ] vanishes for all deviations δΨ from the exact solution. To show this, integrate by parts and use the periodicity restriction(11) on the energy operator. δ Σ,T…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chen and Robicheaux [8] made use of an approximate version of the Floquet R-matrix method to calculate one-and twophoton emission and absorption cross sections and found their results, which were the same as the KWA, differed from the experimental results. Jaron and Kaminski [9] found it was important for small-angle scattering to take into account the effect of the polarization potential. But Milosevic and Ehlotzky [10] were ignored it.…”
Section: Introductionmentioning
confidence: 99%
“…To understand this discrepancy, polarization of the target atom has been studied but shown to have negligible effect [10,13,14]. The theoretical work also involves distorted-wave [12,15,16], Floquet close-coupling [17], R-matrix Floquet [18] and Floquet Lippman-Schwinger [19,20] methods as well as evaluation of the impulse approximation [12,21]. A clear explanation of the experimental results has not yet emerged.…”
Section: Introductionmentioning
confidence: 99%